Socio-Cultural Relationship to Self-Efficacy of Breastfeeding in Pregnant Women in the 3rd Trimester in the Working Area of Imogiri Ist Health Center and Kretek Community Health Center, Bantul Regency - Sulistiawati, Sulistiawati; Dian Ayuningrum, Lia; Dwiarini, Muafiqoh; Lestari, Prasetya; Worawong, Chiraporn (Alma Ata University Press, 2024)
Background: Socio-cultural factors, especially in Javanese society very influence the success and failure of exclusive breastfeeding. Social culture can be in customs, traditions, taboos, etc. Breastfeeding mothers who have low breastfeeding self-efficacy when they later face problems while breastfeeding will tend to make it easier to decide to use alternative techniques for breastfeeding their babies.Objective: To determine the socio-cultural relationship towards breastfeeding self-efficacy in third-trimester pregnant womenMethod: The type of research is a quantitative analytical descriptive. Data collection methods use surveys, observations, or interviews with a cross-sectional approach method. The sampling technique used purposive sampling of as many as 126 respondents with a gestational age of >30 weeks and according to the inclusion criteria. There are 2 instruments used, namely Sociocultural and Breastfeeding Self-efficacy Scale-Short Form (BSES-SF)Results: Based on research conducted on 126 respondents, Social Culture Supports ( 0.000 < 0.05) and Social Culture Does Not Support (0.009 < 0.05) from the Chi-Square test with value 0,000 (p > 0.05) H a rejected means it shows that there is a significant relationship between social culture and breastfeeding self-efficacy. The Breastfeeding Self-Efficacy Score showed that most respondents had high self-confidence ( 82.5 % ).Conclusion: There is a significant relationship between social culture and breastfeeding self-efficacy. In this study, it can be said that respondents in the research area do not have traditions, culture, and taboos that do not support breastfeeding. The majority of respondents with supportive social culture (95%) have high breastfeeding self-efficacy (73%) with quite a large difference from moderate and very low breastfeeding self-efficacy (27%)